Effects of Damping Hole’s Diameter Change of Anti-hunting Damper on Dynamic Performance of High-speed Vehicle - WANG Yixuan; CHEN Enli; QI Zhuang; LIU Pengfei; ZHANG Lin (机车电传动)
In order to research the effect of the damping hole’s change of anti-hunting damper on the vehicle’s stability, running performance and the curve passage capability, the relation between the damper force and the damping hole’s diameter was calculated by the pressure-flow equation. The change of the anti-hunting damper’s diameter was analyzed by software Matlab and imported into software Adams/Rail. The multi-body dynamic models of high-speed vehicle with different damping characteristic were set up in Adams/ Rail. And the models were calculated under various working conditions. Results were that: In terms of the stability of the vehicle, the nonlinear critical velocity of the high-speed train could increase by the influence of the damping hole’s decline. And in terms of the running performance of the vehicle, the wheel/rail lateral force and the lateral ride comfort index were influenced by the change of the damping hole’s diameter significantly. However it had little affect on the derailment and the unloading of the vehicle on curve track.